Septocolumellar Suture Technique for Correction of Septal Caudal Dislocation - Ghulam Murtaza, Sarwat Hassan Syed, Mirza Muhammad Sarwar, Sana Nadeem, Faisal Amin Baig, Mazhar Iftikhar (Journal of Rawalpindi Medical College, 2021)
Objective: To describe this technique for treatment of caudal septal dislocation and to evaluate the effectiveness of this technique in terms of correction of cosmetic deformity and relief of nasal obstruction. Methods: This was a descriptive case series study performed at ENT department of Services Institute of Medical Sciences (SIMS), Services Hospital, Jail Road, Lahore. 30 Cases of mild to moderate degree of septal caudal dislocation were selected and operated. The septum was fixed by sutures to the anterior nasal spine. Columellar pocket was made and septum was sutured in the pocket by two sutures at upper and lower levels to increase the stability of corrected septum. Results: We performed this suturing technique on 30 septoplasty cases during 3 years from Jan-2016 to Jan-2019. Among them 12 (40%) were male and 18 (60%) were female. Total follow up period ranged between 3 to 6 months. Anterior rhinoscopy showed no persistence of deviation or dislocation in 25 patients. 5 cases had mild deviation of septum on non-operated side. Conclusion: Two level septocolomellar suture technique is very effective, easy to learn & perform and shows long term reliability in correction of caudal septal dislocation. This is effective in improving cosmesis and nasal air flow.